Novel Calculators for Risk Stratification in Hepatocellular Carcinoma: A Concise Review. Issue 9 (October 2020) - Pirisi, Mario; Leutner, Monica; Romito, Raffaele; Gaia, Silvia
Abstract : Among clinicians, the users of medical calculators have expanded in recent years to an unprecedented number. The usefulness of some of these calculators is sometimes debatable, and experienced professionals may at times be right in avoiding their use; however, many may simply be unaware of the very existence of medical calculators applicable to their field of interest. The authors felt that this latter scenario might possibly apply to hepatocellular carcinoma (HCC). Hence, the authors concisely reviewed 10 free online medical calculators proposed in the last 8 years, categorizing them on the basis of the purpose for which they were developed (risk of harboring or developing HCC, N=4; prognostication in established HCC, N=6). In addition, the authors tried to establish the success each calculator has had so far in the medical community, by 2 criteria: having been included in the more popular app of medical calculators and being highly cited in the scientific literature. Abstract : Supplemental Digital Content is available in the text.